Studi Kesesuaian Lahan Budi Daya Rumput Laut Eucheuma Cottooni Menggunakan Pendekatan Spasial Multi Kriteria Analisis di Pulau Pelapis - Yada Pratama; Adityo Raynaldo; Robin Saputra (Program Studi Ilmu Kelautan, FIPAK, Universitas OSO, 2024)
The research is aimed at finding a suitable location for sea grass cultivation in the waters of Pelapis Island, Karimata district, North Kayong, West Kalimantan Province. The research was done in June 2023. The method used in this research is quantitative with a field survey approach. The population in this study is the water area of Pelapis Island. The technique in sampling uses Purposive Sampling. The location of the samples is divided into 33 station points, based on the water area of Pelapis Island. The measurements were carried out against 10 water parameters that influenced the growth of seaweed, namely, current speed, brightness, wave, temperature, depth, pH, DO, salinity, nitrate, and posphate. From the overall results of the parameters obtained results with the sum of 2 categories of land suitability i.e. corresponding and not corresponding to the area of the criterion according to 667,201ha 96,47%, and does not correspond to the size of 24,3858ha 3,43%. Based on the results of this research, it can be concluded that the waters of the Pelapis islands are suitable for seagrass farming activities.